Quality control of commercial samples of “arnica” (Arnica montana and Solidago chilensis) from Rio de Janeiro, Brazil - Araújo, Pedro Nogueira; Guimarães, André Luis Alcantara; Moura, Mirian Ribeiro Leite; Vieira, Ana Cláudia de Macêdo (Revista Agrogeoambiental, 2021)
Arnica montana is a medicinal plant native to Europe and used topically to treat contusions, inflammations, and muscular aches. Studies have confirmed the anti-inflammatory activity of extracts of this plant, which can be attributed to the presence of lactones. Its use in Brazil has traditionally been substituted by the species Solidago chilensis, which demonstrates similar therapeutic activity but is more adapted to a tropical climate. It is known that S. chilensis can be used as a substitute for A. montana as they both contain similar active compounds. We acquired eight different commercial brands of “arnica” sold in Rio de Janeiro State, Brazil, in 2013. The analyses of these products were divided into four categories: labeling, macroscopic, microscopic, and microchemical analysis. Labeling analysis followed RDCs (“Resolução de Diretoria Colegiada”) standards (10/2010 through 26/2014). The morphological analyses were performed using microscopic techniques and were followed by microchemical analyses. Our results indicated that none of the samples were in complete conformity with labeling standards, the material was poorly conserved, contaminants were abundantly present, the species were incorrectly identified, and the directions of use were inadequate and potentially dangerous to human health.